1, 2, 3, 4, 6-Penta-O-galloyl-β-D-glucose Inhibits CD44v3, a cancer stem cell marker, by regulating its transcription factor, in human pancreatic cancer cell line. Issue 6 (2nd November 2022) - Kim, Eun-Young; Lee, Seong-Uk; Kim, Yoon Hee
ABSTRACT : Inhibition of cluster of differentiation 44 (CD44), a pancreatic cancer stem cell (CSC) marker, is a potential treatment for pancreatic ductal adenocarcinoma (PDAC). In this study, we evaluated the effect of 1, 2, 3, 4, 6-penta- O -galloyl-β-D-glucose (PGG), a gallotannin contained in various medicinal plants, on CD44 standard (CD44s) and CD44 variant 3 (CD44v3) in Mia-PaCa-2, human pancreatic cancer cells and explored the underlying mechanisms. PGG showed cytotoxic effects and inhibited the proliferation of Mia-PaCa-2 cells. It also inhibited clonogenic activity, adhesion to fibronectin, and cell migration, which are characteristics of CSCs. PGG inhibited the expression of CD44s and CD44v3 by inducing the phosphorylation of p53 and suppressing NF-κB and Foxo3. Inhibition of Foxo3 induces CD44v3 ubiquitination. Indeed, PGG increased proteasome activity and promoted CD44v3 ubiquitination. PGG downregulated the CSC regulatory factors Nanog, Oct-4, and Sox-2, which act downstream of CD44v3 signaling. These data indicate that PGG may have therapeutic effects in pancreatic cancer mediated by inhibition of CSC markers.